Assessing blood flow in uterine fibroids using intravoxel incoherent motion imaging compared with dynamic contrast-enhanced MRI - Sainio, Teija; Saunavaara, Jani; Komar, Gaber; Viitala, Antti; Otonkoski, Saara; Joronen, Kirsi; Perheentupa, Antti; Sequeiros, Roberto Blanco (NATURE PORTFOLIO, 2025)
To assess the utility of IVIM parameters in evaluating uterine fibroid blood flow compared to dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) derived blood flow. Sixteen premenopausal women with uterine fibroids were enrolled in this prospective study. Pelvic MRI scans were obtained for each subject, both with and without continuous intravenous infusion of oxytocin, known to decrease significantly uterine fibroid blood flow, to assess the changes in blood flow of uterine fibroids. IVIM and DCE analyses were conducted using separate dedicated software. The bi-exponential IVIM model was used to estimate perfusion fraction (f), pseudo-diffusion coefficient (D*), and diffusion coefficient (D). DCE blood flow values were derived via T1 perfusion deconvolution arithmetic, utilizing a first pass of an AIF curve. The correlation between the parameters were analyzed by Spearman's rank correlation analysis due to small sample size. Means of the parameters were compared with a nonparametric Wilcoxon sign rank method for each pair. Statistically significant positive correlations were found between perfusion fraction values and DCE blood flow values with oxytocin (Spearson's rho = 0.78, p = 0.0004), and between fD* values and DCE blood flow values with oxytocin (Spearson's rho = 0.64, p = 0.0071). Significant differences in blood flow were detected across most IVIM parameters: f, D*, and fD* (p < 0.001, p = 0.0027, and p = 0.0002, respectively) when comparing the values without oxytocin and with oxytocin. IVIM imaging shows promise for assessing blood flow in uterine fibroids.